DERMATITIS ASOCIADA A Malassezia spp EN UN CONEJO (Oryctolagus cuniculus) CRIADO COMO MASCOTA - Quevedo, Miryam (2013)
Dermatophytosis is the most common mycotic disease in rabbits which is mainly associated to Trichophyton menthagrophytes and Microsporum canis. On the other hand, dermatitis associated to Malassezia spp is rarely reported in lagomorphs. This paper describes a case of dermatitis in a Lop male rabbit of 6 months of age. The animal showed foci of alopecia, skin peeling and hair shedding in three defined areas. A skin sample was cultured in Sabouraud dextrose agar at 25 °C and Malassezia spp was isolated. The animal received an antifungal therapy with griseofulvine obtaining favourable results; however, there was a recurrence and was treated with ketoconazole to fully recover from skin lesions.